Cognitive reserve in frontotemporal degeneration: Neuroanatomic and neuropsychological evidence. (25th October 2016) - Placek, Katerina; Massimo, Lauren; Olm, Christopher; Ternes, Kylie; Firn, Kim; Van Deerlin, Vivianna; Lee, Edward B.; Trojanowski, John Q.; Lee, Virginia M.-Y.; Irwin, David; Grossman, Murray; McMillan, Corey T.
Abstract : Objective: To evaluate if cognitive reserve (CR) contributes to interindividual differences in frontal gray matter density (GMD) and executive impairment that underlie heterogeneity in the disease course of confirmed frontotemporal lobar degeneration (FTLD) pathology. Methods: Fifty-five patients with autopsy confirmation or a pathogenic mutation consistent with underlying tau (FTLD-tau) or TDP-43 (FTLD-TDP) pathology and 90 demographically comparable healthy controls were assessed with T1 MRI and neuropsychological measures (Mini-Mental State Examination, letter fluency, forward digit span, Rey complex figure, and Boston Naming Test). CR was indexed using a composite measure of education and occupation. We used t tests to identify reduced GMD in patients with FTLD relative to controls, regression analyses to relate reduced GMD to CR index, and correlations to relate regions of GMD associated with CR to performance on neuropsychological measures. Results: Patients with FTLD demonstrated impairment on neuropsychological measures. Patients with FTLD exhibited reduced bilateral frontotemporal GMD relative to controls, consistent with the known anatomic distribution of FTLD pathology. Higher CR index was associated with superior letter fluency and with GMD in right dorsolateral prefrontal cortex, orbitofrontal cortex, rostral frontal cortex, and inferior frontal gyrus. Furthermore, we found that higher GMD in frontal regions associated with CR was associated with superior letter fluency. Conclusions: Executive control and verbal ability assessed by letter fluency in FTLD is mediated in part by CR and frontal GMD. The identification of factors influencing cognitive and anatomic heterogeneity in FTLD suggests that CR should be considered in symptom detection, prognosis, and treatment.